1988
DOI: 10.1016/0014-5793(88)80425-3
|View full text |Cite
|
Sign up to set email alerts
|

The conversion of phosphoserine residues to selenocysteine residues on an opal suppressor tRNA and casein

Abstract: This study has been undertaken in order to elucidate the mechanisms of incorporation of Se into glutathione peroxidase (GSHPx), in which seleaocysteine corresponds to the opal termination codon UGA on the mRNA. We studied the above mechanisms using an opal suppressor tRNA, prepared from bovine liver, and caseia as a model protein for the GSHPx apo-enzyme which might contain phosphoserine. The results showed that opal suppressor tRNA did not accept seleaocysteine (lower than 0.1 mmol/mol) under the standard con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The minor phosphoseryl-tRNA and another minor seryl-tRNA identified in bovine, rabbit, and chicken livers that decoded the stop codon UGA (12) were shown to be Sec tRNA [Ser]Sec (13). It was subsequently reported that phosphoseryl-tRNA [Ser]Sec was the intermediate in the biosynthesis of Sec in mammals (21,22) and in bacteria (23). However, after the identification of aminoacryltRNA [ (26).…”
Section: Discussionmentioning
confidence: 99%
“…The minor phosphoseryl-tRNA and another minor seryl-tRNA identified in bovine, rabbit, and chicken livers that decoded the stop codon UGA (12) were shown to be Sec tRNA [Ser]Sec (13). It was subsequently reported that phosphoseryl-tRNA [Ser]Sec was the intermediate in the biosynthesis of Sec in mammals (21,22) and in bacteria (23). However, after the identification of aminoacryltRNA [ (26).…”
Section: Discussionmentioning
confidence: 99%
“…Following the landmark discovery of E. coli tRNA Sec in 1988 (7), it was speculated that Sep-tRNA might be an intermediate in Sec-tRNA Sec formation (8). In vitro synthesis of glutathione peroxidase in mouse extracts suggested that this was the case (33). However, the successful identification and characterization of E. coli SelA, the selenocysteine synthase that catalyzes SectRNA Sec formation directly from Ser-tRNA Sec (Fig.…”
Section: Sep-trna Is An Intermediate In Sec Biosynthesis In Eukaryotementioning
confidence: 99%
“…Examination of the base sequence adjacent to the UGAs in the GPX and in formate dehydrogenase does not readily reveal a "consensus sequence" of bases that would differentiate a [Se]Cys-UGA from a termination UGA. To allow UGA to specify [Se]Cys rather than chain termination, Mizutani & Hitaka (52) proposed that a stem motif at the UGA was important. Mullenbach et al (55) have proposed that a lack of an adjacent stem motif may be critical.…”
Section: Cotranslational Se Incorporationmentioning
confidence: 99%